How to promote the development of a green economy: Talent or technology?—Evidence from China’s high-speed rail - Kang, Dongliang; Zhai, Xiaoyi; Chen, Fengwen; Wang, Wei; Lu, Jia (Frontiers in Psychology, 2022)
Green economy is an important element to support sustainable economic development, and relies on talents and technologies. Under the framework of traditional economic theory, this study explores the impact of high-speed rail and innovation on green economy from the perspective of talent and technology. Using the data of 281 prefecture-level cities in China from 2008 to 2018, this study constructs empirical models to discuss the driving factors of green economy. The empirical results show that high-speed rail and innovation can promote the development of green economy, and the opening of high-speed rail can strengthen the positive association between innovation and green economy. The accessibility of high-speed rail improves the flow of talent between different cities, and greatly stimulates the positive impact of innovation on green economic activities. In the further test, this study explores the impact of high-speed rail and innovation on green economy from different dimensions, including government policy, economic strength and administrative level. During China’s 12th Five-Year Plan, high-speed rail and innovation have a positive impact on green economy, but the impact of innovation can be still significant after this period. Moreover, the opening of high-speed rail may motivate the migration of talents from developed cities to developing cities, while developed cities can rely on technological advantages to support green economic activities. Furthermore, low administrative level cities will rely on attracting more talents to promote green economy due to their technological disadvantages, and innovation can play a critical role in enhancing the green economy of high administrative level cities. The talent and technology are both important to green economic activities, and the construction of high-speed rail change the impact of technology on green economy through the flow of talents. Our findings can explain why the opening of high-speed rail can promote the development of green economy, and effectively help governments achieve the goal of sustainable development.